2010
DOI: 10.1111/j.1440-1819.2009.02052.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of alexithymia and temperament and character dimensions with lifetime post‐traumatic stress disorder in male alcohol‐dependent inpatients

Abstract: Aims:The purpose of the present study was to evaluate the prevalence of lifetime post-traumatic stress disorder (PTSD) in male alcohol-dependent inpatients and to investigate the relationship of PTSD with alexithymia and temperament and character dimensions.Methods: Participants were 156 consecutively admitted male alcohol-dependent subjects. Patients were investigated using the Clinician-Administered PTSD Scale (CAPS), the Toronto Alexithymia Scale (TAS-20) and the Temperament and Character Inventory (TCI).Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 58 publications
3
27
0
Order By: Relevance
“…These observations not only add new evidence to the link between novelty seeking and the development of PTSD-like symptoms (Evren et al, 2010; Jakšić et al, 2012; Richman and Frueh, 1997; Wang et al, 1997), they suggest that novelty seeking can predict some aspects of an individual’s response to fear following exposure to a traumatic stressor. The HR/LR model thereby appears as a valuable tool with predictive value for the investigation of individual differences in vulnerability to the development of PTSD-like symptoms.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…These observations not only add new evidence to the link between novelty seeking and the development of PTSD-like symptoms (Evren et al, 2010; Jakšić et al, 2012; Richman and Frueh, 1997; Wang et al, 1997), they suggest that novelty seeking can predict some aspects of an individual’s response to fear following exposure to a traumatic stressor. The HR/LR model thereby appears as a valuable tool with predictive value for the investigation of individual differences in vulnerability to the development of PTSD-like symptoms.…”
Section: Discussionmentioning
confidence: 72%
“…Notably, this association is further supported in animal models of individual differences in emotional response in which, for instance, predisposition to learned helplessness is predicted by novelty seeking and associated with differences in anxiety-like behaviors, acquisition of cued fear conditioning, and impaired fear extinction (Padilla et al, 2010; Shumake et al, 2005). Moreover, in combination with other personality traits, a few reports denote a predictive value for novelty seeking in PTSD vulnerability and symptoms vulnerability (Evren et al, 2010; Gil, 2005; Jakšić et al, 2012; Richman and Frueh, 1997; Wang et al, 1997), conferring both a preclinical and clinical relevance to the HR/LR model and individual differences in novelty seeking in a PTSD context. In addition, based on baseline differences in a behavioral paradigm with minimal impact on further experimental manipulations, the HR/LR model provides an interesting framework for the study of individual differences in vulnerability to the development of PTSD symptoms following exposure to traumatic stressor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because, according to their results, alexithymia seems more connected to posttraumatic symptoms than to trauma exposure itself, they conclude that alexithymia might be a preexisting condition that increases the probability of developing PTSD (Yehuda et al, 1997). Other studies showed that the inability to identify one's own feelings is highly congruent with the construct of PTSD (Evren, Dalbudak, Cetin, Durkaya, & Evren, 2010; Sondergaard & Theorell, 2004). Several studies indicate a phenomenological overlap between emotional numbing as a symptom of PTSD and alexithymia, which is also characterized by disordered affect regulation (Badura, 2003; Declercq et al, 2010; Fukunishi et al, 1996).…”
mentioning
confidence: 99%
“…In Cloninger's model, a low self-directedness score is an indicator of poor individual maturity and of an enhanced risk of personality disorder without specificity to the underlying types of personality . Other studies have already shown that this trait is lower for OCD patients when compared to healthy subjects (Bejerot et al, 1998;Kusunoki et al, 2000;Lyoo et al, 2001;Alonso et al, 2008;Kim et al, 2009;Cruz-Fuentes et al, 2004) as well as subjects with social phobia (Pelissolo et al, 2002), panic disorder (Wachleski et al, 2008) or post-traumatic stress disorder (Evren et al, 2010) although without direct comparisons between these groups. However, in our study, the SD difference between AD and OCD groups seems to be due to a state effect and it is no longer significant when depressive symptoms (and age) are taken into account.…”
Section: Discussionmentioning
confidence: 94%